A membrane-based fluorescence-quenching immunochromatographic sensor for the rapid detection of tetrodotoxin. (November 2017) - Shen, Haicong; Zhang, Shiwei; Fu, Qiangqiang; Xiao, Wei; Wang, Shifeng; Yu, Shiting; Xiao, Meng; Bian, Hongfen; Tang, Yong
Abstract: A membrane-based fluorescence-quenching immunochromatographic sensor (FQ-ICS) was developed to detect tetrodotoxin (TTX) in as little as 12 min by utilizing fluorescence resonance energy transfer (FRET). Compared with traditional ICS for detecting TTX, this FQ-ICS provided a positive readout of the signal intensity as well as higher sensitivity. The signal detected during tests increased along with increasing TTX concentrations within a determinate concentration range. The limit of detection (LOD) of the method was 0.78 ng/mL, a value more than 20 times lower than the latest reported value using colloidal gold strips for TTX detection. Furthermore, the detection linear range (DLR) was 3.13–50 ng/mL. Recovery rates for the FQ-ICS used to detect TTX in spiked samples ranged from 61.3% to 70.4%. These results indicate that the FQ-ICS is highly sensitive and suitable for the rapid detection of TTX. Highlights: A fluorescence-quenching strip was applied to rapid, positive readout, and high sensitive tetrodotoxin detection. This strip provided a turn-on readout mode of fluorescence signal, which was more consumer-friendly. The visual detection limit of the strip was 20 times lower than colloidal gold strip for tetrodotoxin detection.